Enhancing Learners' Character Development: Insights from Utilizing Learning Materials and Teaching-Learning Activities in TEFLIN - Sukarno, Sukarno; Riyadini, Maria Vineki (Universitas Pendidikan Mandalika, 2024)
The pedagogy of Teaching English as a Foreign Language in Indonesia (TEFLIN) underscores the significance of substantive content in language instruction. This paper elucidates the pivotal role of integrating culturally relevant materials into English teaching-learning curricula to effectively develop students’ linguistic competence and linguistic performance. Drawing upon the symbiotic relationship between language and culture, the discourse explores how native speakers' cultural nuances in instructional materials catalyze students' linguistic competence and character development. Central to this approach is the recognition that language acquisition encompasses understanding the cultural underpinnings inherent in communication. This study delves into the pedagogical framework wherein the exploration and elucidation of linguistic features within input texts serve as conduits for delving into students' indigenous wisdom, thereby fostering character-building opportunities. However, successfully integrating these materials for character development hinges upon educators' adeptness in devising contextually relevant teaching-learning activities. Emphasizing the intrinsic moral values interwoven within instructional materials, this paper delineates a structured approach to character development through TEFLIN. Based on experiential insights, this article delineates a procedural framework for leveraging learning materials and teaching-learning activities within TEFLIN to nurture character traits. The outlined phases encompass pre-teaching rituals to set a conducive learning environment, interactive pedagogical approaches during instruction, and reflective post-teaching assessments. Educators are empowered to cultivate a culture of ethical consciousness and character refinement among students by accentuating the integration of moral values throughout the instructional process.